AFFINITY CHROMATOGRAPHY OF RABBIT GASTROCNEMIUS ALPHA-L-FUCOSIDASE - Khan, J.A.; Lewis, M.H.R. (Journal of Ayub Medical College Abbottabad, 2024)
Abstract: Ct-L-Fucosidase was purified from rabbit gastrocnemius muscle using agarose-e-aminocaproyl-fucosamine. The isolated enzyme was found to be pure by a number of different analytical techniques including gel electrophoresis. The purified enzyme was found essentially free of other glycosidases. The main characteristics of the purified Î±-L-Fucosidase were determined; pH 6.0-6. 3, KmO.52, Vmax 25.13 n mol/gm protein/min., Ki 0.46. L-fucosq was the only physiological competitive inhibitor of the enzyme. Ct-L-fucosidase is heat labile and stable for 2-3 months at - 20 C in the presence of lOOmM L-fucose. The purified enzyme showed 50,000 Mol. Wt. on SDS-Electrophoresis.